Neuronal abnormalities in microtubule-associated protein 1B mutant mice. - Edelmann, W (1996)
Microtubules play an important role in establishing cellular architecture. Neuronal microtubules are considered to have a role in dendrite and axon formation. Different portions of the developing and adult brain microtubules are associated with different microtubule-associated proteins (MAPs). The roles of each of the different MAPs are not well understood. One of these proteins, MAP1B, is expressed in different portions of the brain and has been postulated to have a role in neuronal plasticity and brain development. To ascertain the role of MAP1B, we generated mice which carry an insertion in the gene by gene-targeting methods. Mice which are homozygous for the modification die during embryogenesis. The heterozygotes exhibit a spectrum of phenotypes including slower growth rates, lack of visual acuity in one or both eyes, and motor system abnormalities. Histochemical analysis of the severely affected mice revealed that their Purkinje cell dendritic processes are abnormal, do not react with MAP1B antibodies, and show reduced staining with MAP1A antibodies. Similar histological and immunochemical changes were observed in the olfactory bulb, hippocampus, and retina, providing a basis for the observed phenotypes.